2008
DOI: 10.1093/aje/kwn067
|View full text |Cite
|
Sign up to set email alerts
|

Low Workplace Social Capital as a Predictor of Depression: The Finnish Public Sector Study

Abstract: In a prospective cohort study of Finnish public sector employees, the authors examined the association between workplace social capital and depression. Data were obtained from 33,577 employees, who had no recent history of antidepressant treatment and who reported no history of physician-diagnosed depression at baseline in 2000-2002. Their risk of depression was measured with two indicators: recorded purchases of antidepressants until December 31, 2005, and self-reports of new-onset depression diagnosed by a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
158
4
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(175 citation statements)
references
References 32 publications
9
158
4
4
Order By: Relevance
“…Marital status is also associated with psychiatric health outcomes. Never being married, widowed, or divorced are associated with higher suicide rates (Masocco et al, 2008) as well as higher risk of depression (Akhtar-Danesh & Landeen, 2007, Kouvonen et al, 2008, Romans, Cohen & Forte, 2011. It is thus plausible that an association between marital status and mental health is present in the more general population for obvious reasons of loneliness, lack of emotional support and lack of practical support in everyday life.…”
Section: Introductionmentioning
confidence: 99%
“…Marital status is also associated with psychiatric health outcomes. Never being married, widowed, or divorced are associated with higher suicide rates (Masocco et al, 2008) as well as higher risk of depression (Akhtar-Danesh & Landeen, 2007, Kouvonen et al, 2008, Romans, Cohen & Forte, 2011. It is thus plausible that an association between marital status and mental health is present in the more general population for obvious reasons of loneliness, lack of emotional support and lack of practical support in everyday life.…”
Section: Introductionmentioning
confidence: 99%
“…Measures such as registry information on hospital overcrowding, reorganization, and workload (12)(13)(14), expert assessment (10,15), employer assessment (16), job title (17), and averaging across work units (8,18,19) or workplaces (20) are different approaches to this problem.…”
mentioning
confidence: 99%
“…In a Finish study low individual-level social capital (but not aggregate workplace-level social capital) was associated with self-reported depression [39]. Individual-level social capital has been shown to be associated with exposure to "gossip and slandering" in the workplace [30] and impairment of self-rated health [40] to a higher degree than workplace-level social capital.…”
Section: Discussionmentioning
confidence: 96%
“…Common features of organizational social capital include mutual trust, organizational justice and fairness as well as the ability to cooperate or collaborate towards a collectively, shared goal [34,35,38]. Prospective studies have shown that low (self-reported) individual-level ratings of organizational social capital is associated with higher levels of self-reported depression [39], while low organizational social capital at both the individual and work unit level is associated with higher risks of poor health [40]. A 1-year follow-up study furthermore found that increased workplace social capital was associated with lower levels of psychological distress [41].…”
Section: Introductionmentioning
confidence: 99%